Legal Certainty of Interfaith Marriage After SEMA No. 02 of 2023 Maqasid Sharia Perspective - Shabrina Rusliansyah; Hasnul Arifin Melayu; Aulil Amri; Claire Lajaunie; Fatima Zohra Benali (An-Nisa: Journal of Islamic Family Law, 2025)
Interfaith marriage in Indonesia has long been a controversial legal issue, particularly following the issuance of Supreme Court Circular Letter (SEMA) No. 02 of 2023, which explicitly prohibits the registration of marriages between individuals of different religions. This policy has raised significant concerns regarding legal certainty and its alignment with substantive justice, especially when examined through the lens of Maqasid al-Sharia. This study aims to analyze the extent of legal certainty governing interfaith marriage under Indonesia’s positive law framework and to assess its conformity with the objectives of Islamic law. Employing a normative juridical method, this research utilizes statutory, conceptual, and doctrinal approaches, drawing upon legislation, Islamic legal doctrines, and relevant academic literature. The findings reveal that, under positive law, interfaith marriage lacks formal legal validity as it contravenes Article 2 paragraph (1) of Law No. 1 of 1974 on Marriage, a position further reinforced by SEMA No. 02 of 2023 as a binding judicial guideline. From the perspective of Maqasid al-Sharia, the prohibition is consistent with the protection of the five essential objectives of Islamic law (al-daruriyyat al-khams), particularly the preservation of religion (hifz al-din) and lineage (hifz al-nasl). Nevertheless, this study also identifies inconsistencies in the implementation of SEMA No. 02 of 2023 at the practical level, which may undermine legal certainty and result in unequal legal treatment. Therefore, this research recommends the strengthening of legal harmonization through clearer statutory regulation, enhanced inter-institutional coordination, and improved guidance for law enforcement and civil registration authorities to ensure consistent application in accordance with the principles of legal certainty, justice, and social welfare.